Probation counseling for substance use disorders in Romania: An analysis of challenges and opportunities - Ilie, Cristina (European journal of probation, 2024)
The article aims to analyze the intervention techniques used in probation services when working with convicted persons with substance use disorders, and it is structured in two directions. The first direction includes the theoretical analysis of the concept of “substance use disorders” and the specific interventions used in the probation system. The second part of the paper highlights the results of a sociological survey based on a questionnaire administered to probation counselors in Romania. This survey highlights the strengths and weaknesses of intervention with people suffering from substance use disorders and provides a set of recommendations for counselors to apply in their work with this category of beneficiaries.